Case report: A complex case of valve-in-valve TAVI and left bundle branch pacing for severe aortic regurgitation with partially corrected type A aortic dissection and low ejection fraction - Mihailovič, Peter Marko; Žižek, David; Vitez, Luka; Holc, Primoz; Klokočovnik, Tomislav; Bunc, Matjaž (Frontiers in Cardiovascular Medicine, 2023)
Background Aortic regurgitation is a major concern following transcatheter aortic valve implantation (TAVI), as even low-grade regurgitation is associated with increased mortality. This is of particular concern to patients with pre-existing aortic disease who are at increased risk of TAVI valve slippage. Furthermore, conduction system disturbances after TAVI, namely left bundle branch block (LBBB), may have an additional detrimental effect on cardiac function. Case presentation This report documents a successful treatment strategy in a frail patient with a bicuspid aortic valve and aortic disease after valve-sparing surgical repair in 1998, who subsequently developed aortic stenosis and underwent TAVI with an Evolut R self-expanding aortic valve. The progression of aortic disease, aortic root dilatation, and leaflet degeneration over the following years caused aortic regurgitation of the self-expanding aortic valve, resulting in left ventricular dilatation and heart failure along with LBBB and left ventricular (LV) mechanical dyssynchrony. Diagnostic workup of the patient showed persistence of the aneurysm distal to the graft with a dissection spanning the ascending aorta, arch, and terminating proximal to the aortic isthmus. After consideration by the cardiac team, a balloon-expandable valve was chosen for a valve-in-valve (ViV) procedure to provide sufficient radial force to expand the existing valve and correct the regurgitation. Due to the anatomy, a J-wire and pigtail catheter were successfully used for a safe approach and placement of the valve. Following the procedure, intermittent complete atrioventricular block was observed in addition to the pre-existing left bundle branch block, necessitating resynchronization pacing. Due to anatomical considerations, ease of placement, and the expected good level of resynchronization due to the proximal block, we opted for left bundle branch pacing, which showed improvement in left ventricular dyssynchrony and LV function at follow-up. Conclusion Valve-in-valve implantation of a balloon-expandable Myval TAVI device to treat aortic regurgitation caused by slippage and right leaflet disfunction of slef valve is feasible in challenging anatomical scenarios. Left bundle branch pacing is a viable alternative to correct mechanical dyssynchrony in complex patients with LBBB and anatomical challenges necessitating resynchronization.